Larangan Pemakaian Cadar Di Kampus Dalam Perspektif Prinsip Persamaan Kedudukan di depan Hukum - Haris Kurnia Anjasmana; Hernadi Affandi (Nagari Law Review, 2019)
The prohibition on the use of veils in some campuses raises the pros and cons in the community, coupled with the many khilafiyah debates regarding the law on the use of veils. The identification of the problem in this article is first how the law of the use of veils in Islam, secondly whether the prohibition on the use of veils on campus violates the principle of equality before the law. The method used is juridical normative with comparative approach method and conceptual approach. The writing specifications used are descriptive analytical. The results of this paper are Basically, the use of legal veils is permissible. Related to the ban on the use of veils on several campuses, the authors argue that it is okay to keep the good name of the campus and avoid abuse of veils from all forms of radicalism, intolerance, or fraud in the lecture process. But before the ban was put into effect, it should first be with discussion and even research involving the entire academic community related to the positive or negative veil on campus by using data and reference sources that can be trusted scientifically and academically and also pay attention to the values that live in society.